Avaliação da atenção básica à saúde da criança em unidades básicas de saúde no estado de São Paulo - Sanine, Patricia Rodrigues [UNESP] (2014)
The quality of health care provided to children plays an important role in risk control and vulnerability reduction during childhood. Child health is among the most traditional and better structured actions in Primary Care (APS) in the State of São Paulo, but some indicators still point to low performance of provided care, such as an increasing number of congenital syphilis cases in the State. The present study assesses the quality of the organization and local management of child health care actions in Basic Health Care Units (UBS) in the State of São Paulo. We used a database built with QualiAB in an evaluation of APS services in 2010. The evaluation prioritized APS services in municipalities with less than 100,000 inhabitants, which participated voluntarily in the study. We studied 31 issues concerning child health care. Out of a universe of 2,735 APS units, 2,687 provided child health care. All frequencies were analyzed and distributed according to: type of service (USF, “traditional” UBS, UBS with ESF/ACS and Ohers), team composition (with or without a pediatrician) and application or not of benzathine benzylpenicillin. The analyzes allowed us to observe the predominance of actions advocated in USFs, even those without a pediatrican in the team. Among the actions aimed at children it is worth mentioning: medical consultation (98%); nursing consultation (80.3%); vaccination (77.6%); educational actions in the community (93.4%); odontological care for babies (36.6%), odontological care for children up to 6 year old (46,9%) and for schoolchildren (54.4%); clinical samples collection for laboratory tests (68%) and drug dispensation (85.1%). Among the actions planned in child health care some conditions are tackled less frequently, such as schoolchildren health (33.9%), child respiratory infections (57%) and violence (30.8%). Other conditions, more traditional, are tackled more often, like breastfeeding (87.3%), childcare (87.7%) ...